Morphological, Molecular Structural and Physicochemical Characterization of Starch Granules Formed in Endosperm of Rice with Ectopic Overexpression of α-Amylase - Zhang, Kuo; Nakamura, Sumiko; Ohtsubo, Ken-ichi; Mitsui, Toshiaki (Journal of applied glycoscience : JAG, 2024)
The objective of this study was to characterize the endosperm starch in rice that ectopically overexpressed the α-amylase. Transgenic rice plants, transformed with cauliflower mosaic virus 35S promoter driven AmyI-1 (35S::AmyI-1) and AmyII-4 (35S::AmyII-4), and 10 kDa prolamin promoter driven AmyI-1 (P10::AmyI-1), were cultivated under standard conditions (23 °C, 12 h in the dark/ 26 °C, 12 h in the light), and brown grains were subsequently harvested. Each grain displayed characteristic chalkiness, while electron microanalyzer (EPMA)-SEM images disclosed numerous small pits on the surface of the starch granules, attributable to α-amylase activity. Fluorescence labeling and capillary electrophoresis analysis of starch chain length distribution revealed no significant alterations in the starches of 35S::AmyI-1 and 35S::AmyII-4 transgenic rice compared to the wild-type. Conversely, the extremely short α-glucan chains (DP 2-8) exhibited a dramatic increase in the P10::AmyI-1 starch. Rapid visco-analyzer analysis also identified variations in the chain length distribution of P10::AmyI-1 starch, manifesting as changes in viscosity. Moreover, 1H-NMR analysis uncovered dynamic modifications in the molecular structure of starch in rice grain transformed with P10::AmyI-1, which was found to possess unprecedented structural characteristics.